The chronology of a large ice-dammed lake and the Barents-Kara ice sheet advances, northern Russia. - Mangerud, Jan; Astakhov, Valery I; Murray, Andrew Sean; Svendsen, John Inge (PANGAEA, 2001)
Beach and shoreface sediments deposited in the more than 800-km long ice-dammed Lake Komi in northern European Russia have been investigated and dated. The lake flooded the lowland areas between the Barents-Kara Ice Sheet in the north and the continental drainage divide in the south. Shoreline facies have been dated by 18 optical stimulated luminescence (OSL) dates, most of which are closely grouped in the range 80-100 ka, with a mean of 88 +/- 3 ka. This implies that that the Barents-Kara Ice Sheet had its Late Pleistocene maximum extension during the Early Weichselian, probably in the cold interval (Rederstall) between the Brørup and Odderade interstadials of western Europe, correlated with marine isotope stage 5b. This is in strong contrast to the Scandinavian and North American ice sheets, which had their maxima in isotope stage 2, about 20 ka. Field and air photo interpretations suggest that Lake Komi was dammed by the ice advance, which formed the Harbei-Harmon-Sopkay Moraines. These has earlier been correlated with the Markhida moraine across the Pechora River Valley and its western extension. However, OSL dates on fluvial sediments below the Markhida moraine have yielded ages as young as 60 ka. This suggests that the Russian mainland was inundated by two major ice sheet advances from the Barents-Kara seas after the last interglacial: one during the Early Weichselian (about 90 ka) that dammed Lake Komi and one during the Middle Weichselian (about 60 ka). Normal fluvial drainage prevailed during the Late Weichselian, when the ice front was located offshore.
Age determination of sediment from Lake Komi
Keywords: agedetermination; Bolotny_Mys; Bolotny Mys; Byzovaya Ravine; Byz-rav; Garevo; Novik-Bozh; OUTCROP; Outcrop sample; Ozornoye; Pechora1997; Quaternary Environment of the Eurasian North; QUEEN; QUEEN_Exped; Russia; Sampling on land